Pengaruh Proses Pembelajaran Daring Pada Masa Pandemi Covid-19 Terhadap Perilaku Belajar Siswa Kelas Tinggi Di Sd Negeri 6 Kendari - Fifi Sandra; Ahmad Ahmad; Hesti Hesti (Prodi PGSD Unsultra, 2021)
The purpose of this study was to determine the effect of online learning processes during the Covid-19 pandemic on the learning behavior of upper-grade students at SD Negeri 6 Kendari. This research used a quantitative approach. The population consisted of 412 students, with a sample of 62 students. The data were analyzed using a simple linear regression method. The findings show that students’ learning behavior tended to be in the low category with a percentage of 33.87%. The SPSS output indicated a coefficient of determination (R Square) of 0.873, which means that the online learning process variable influenced students’ learning behavior by 87.3%. The regression equation obtained was Y = 1.078 + 0.966X, indicating that if there were no online learning process, students’ learning behavior would be around a score of 1.078. The conclusion of this study is that the online learning process during the Covid-19 pandemic had a significant effect on the learning behavior of upper-grade students at SD Negeri 6 Kendari by 87.3%.